NOVEL CANDHIKALA KAPURANTA SEBAGAI ALTERNATIF PENYELESAIAN DEHUMANISASI PADA ERA INTERNET OF THINGS (IOT) - Pebryawan, Krisna; Tukiyo, Tukiyo (JURNAL PESONA, 2018)
AbstractThis study aims to describe the cultural value in Candhikala Kapuranta novel as an alternative to dehumanization settlement in IoT era. The research method used is qualitative descriptive. The data source used is Candhikala Kapurantas novel by Sugiarto Sriwibawa. Data collection techniques used is the technique of referring note, while the technique of data analysis using interactive analysis techniques. Based on the research that has been done, the results of his research as follows. First, the cultural values in Candhikala Kapurantas novel include religious values and social values. Second, dehumanization in the IoT era is individualism, pornography, and intolerance. Thirdly, the cultural values contained in Candhikala Kapurantas novel as an alternative to dehumanization settlement in the IoT era.Keywords: Cultural Values, Dehumanization, Era IoT, Novel